Identification of amino acid residues in the MT-loop of MT1-MMP critical for its ability to cleave low-density lipoprotein receptor - Wang, Maggie; Alabi, Adekunle; Gu, Hong-mei; Gill, Govind; Zhang, Ziyang; Jarad, Suha; Xia, Xiao-dan; Shen, Yishi; Wang, Gui-qing; Zhang, Da-wei (Frontiers in Cardiovascular Medicine, 2022)
Low-density lipoprotein receptor (LDLR) mediates clearance of plasma LDL cholesterol, preventing the development of atherosclerosis. We previously demonstrated that membrane type 1-matrix metalloproteinase (MT1-MMP) cleaves LDLR and exacerbates the development of atherosclerosis. Here, we investigated determinants in LDLR and MT1-MMP that were critical for MT1-MMP-induced LDLR cleavage. We observed that deletion of various functional domains in LDLR or removal of each of the five predicted cleavage sites of MT1-MMP on LDLR did not affect MT1-MMP-induced cleavage of the receptor. Removal of the hemopexin domain or the C-terminal cytoplasmic tail of MT1-MMP also did not impair its ability to cleave LDLR. On the other hand, mutant MT1-MMP, in which the catalytic domain or the MT-loop was deleted, could not cleave LDLR. Further Ala-scanning analysis revealed an important role for Ile at position 167 of the MT-loop in MT1-MMP’s action on LDLR. Replacement of Ile167 with Ala, Thr, Glu, or Lys resulted in a marked loss of the ability to cleave LDLR, whereas mutation of Ile167 to a non-polar amino acid residue, including Leu, Val, Met, and Phe, had no effect. Therefore, our studies indicate that MT1-MMP does not require a specific cleavage site on LDLR. In contrast, an amino acid residue with a hydrophobic side chain at position 167 in the MT-loop is critical for MT1-MMP-induced LDLR cleavage.